To Examine the Factors Affecting the Investment of Private Education in China - Li, Ye (2013)
On the basic of summary of literatures about investment climate and non-government education, the dissertation analyzes current conditions of non-government education, and explores its economic characteristics, growth stage, functions, and the way for private investment to participate in education. The dissertation classifies climate factors that may influence non-government education into eight investment climate factors on the basis of the viewpoint of macroeconomics and the results of literature review, and investigation, then makes hypothesizes of these factors. Using the Panel Data of 8 fundamental economic variables of 31 provinces of China in about 6 years. This dissertation analyzes the relationship between climate factors and non-government education investment. It reveals that, during all the period, there is no statistical contradiction between the empirical result and hypothesizes. Having finished research of the degree and direction of the influence of these investment climate factors, this dissertation evaluates the investment climate in different areas with the Generalization Principle Component Analysis. The result shows that the first 7 areas scores high are Beijing, Shanghai, Zhejiang, Guangdong, Jiangsu, Tianjin, Shandong. The scores are high and consistent, which indicates that compared with other locations, these areas are more suitable for investment in non-government education, and have sustainable favorable non-government investment climate.